Pemanfaatan Alat Permainan Edukatif untuk Melatih Fokus dan Konsentrasi Anak Autisme Spectrum Disorder (ASD) di Sekolah Luar Biasa - Munir, Nilam; Mursalin, Nur Rahmatan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Therapy using educational game tools (APE) has emerged as a promising approach to assist children with Autism Spectrum Disorder (ASD). Methods: participatory action research (PAR), conducted at SLB Autism Siti Nurdaya Soppeng. The program consists of two primary activities: (1) training for 20 participants, including teachers and parents, and (2) direct assistance to students with ASD, with 3 subjects observed based on their autism severity levels: mild, moderate, and severe. The therapy sessions, lasting 45 minutes, were divided into two sessions. Results: (1) Severe ASD Subject (SAB): In Session 1, the average score was 17.4 (categorized as fair), which increased to 22.4 (still categorized as fair) in Session 2, with a notable preference for constructive play activities. (2) Moderate ASD Subject (SAS): The average score in Session 1 was 18 (categorized as fair), showing significant improvement in Session 2, with an average score of 28.6 (categorized as good), and a preference for constructive play activities. (3) Mild ASD Subject (SAR): The average score in Session 1 was 32.4 (categorized as very good), which increased to 34.4 in Session 2 (still categorized as very good), with a preference for beading activities. Conclusions: , the program demonstrates that APE-based therapy contributes positively to enhancing focus and concentration in children with varying levels of ASD colon